Analisis Kerusakan Jalan Menggunakan Metode Surface Distress Index dan Pavement Condition Index (Studi Kasus: Ruas Simpang Jembatan Lamnyong - Cot Iri) - Yusputri, Rafiqa Muhnita; darma, yusria; Saleh, Sofyan M; Nasri, Wan Adam (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
Good road quality is essential to ensure comfort, safety, and efficiency in transportation, yet roads are prone to damage from extreme weather, heavy traffic loads, and environmental factors. The Simpang Jembatan Lamnyong - Makam T. Nyak Arief - Cot Iri road experiences high traffic volume, resulting in damage at several points and reducing its overall performance. To address this issue, proper identification of road damage is necessary to determine suitable repair methods. This study aims to determine the difference in the level of damage using two different methods. Field data were collected through direct surveys, recording types and dimensions of damage across a 4.4 km stretch from STA 0+000 to STA 4+400, segmented every 100 meters. The results showed that SDI values ranged from 0 to 125, with an average of 64 categorized as “moderate,” while PCI values ranged from 0 to 100, with an average of 27 categorized as “poor.” Based on this comparison, the PCI method is considered more accurate, as it evaluates a wider range of damage types in greater detail. Therefore, the PCI method is recommended as the preferred approach for assessing road damage and guiding maintenance decisions on similar road sections.